Comparison of prognostic value of different clinical scales for predicting early lethal outcome after acute spontaneous supratentorial intracerebral hemorrhage - Kuznietsov, A. A.; Kozyolkin, O.; Кузнєцов, Антон Анатолійович; Козьолкін, Олександр Анатолійович (John Wiley & Sons, Ltd., 2017)
Background and aims: Identification of vital prognosis in patients with acute spontaneous supratentorial intracerebral hemorrhage (ASSICH) using clinical parameters is very important and relevant in modern angioneurology and can help the practicioners to improve treatment approaches. Therefore we decide to verify the clinical scale with the largest prognostic value for predicting early lethal outcome (ELO) after ASSICH.